Factors associated with induced abortion among women attending Marie Stopes Clinics in Kathmandu Valley - Thapa, Nilu; Maharjan, Sajana (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Though abortion has been legalized in Nepal from September 2002 but it is still a highly stigmatized issue with lots of prevailing misconceptions in the community. In this scenario also each year one lakh abortion are done in Nepal and the number of women seeking abortion services is in increasing trend. Therefore, it is very important to know the reasons behind seeking abortion services by Nepalese women. The overall objective of this study was to assess the factors associated with induced abortion among women attending at Marie Stopes Clinics of Kathmandu Valley. MATERIAL AND METHODS: A descriptive cross-sectional study was carried out over a period of two weeks in the Marie Stopes's clinics of Gongabu and Kupondole sites of Kathmandu among 85 purposively selected women. Face-to-face interview was done by using the semi-structured questionnaire. The collected data was analyzed by using simple descriptive statistics like percentage, frequency, mean and standard deviations and presented in the forms of tables and narratives. RESULTS: The mean age of the respondents with standard deviation was 25.5±5.571 years. Around 88 % of the respondents were literate. Majority (91.8%) were married. Around 75 % of the respondents cited, having enough children and wanting no more child now as the main reason behind having abortion. The decision of undergoing abortion was taken by both partners in 89.4% of the respondents. Exactly 62.4% of the respondents were not aware about the possible effects of abortion. Almost 32% of the respondents had the history of previous abortion. Almost 90 % of the respondents had desired to use contraceptive after abortion. Condoms, pills and Depo-Provera were preferred by 41.3%, 22.7% and 13.3% of the respondents for use after undergoing abortion respectively. CONCLUSION: It can be concluded from the study that the major reasons behind undergoing abortion were to limit the number of children and desire to postpone the children. About one-third of women have the history of previous abortion and similar proportion has done abortion two to three times. Therefore, this study suggests that long acting FP methods and sterilization services should be made accessible to women so that they could prevent unwanted pregnancy. Also there is need of strengthening counseling services for contraceptive use to women coming for abortion repeatedly.